Geopolitics and Ethical Literacy in the Transformation of Public Officials’ Behavior in Indonesia - Muhammad Bahruddin; Nur Hidayat; Nanang Endrayanto (The International Journal of Interdisciplinary Global Studies, 2026)
Indonesia’s strategic position in Indo-Pacific economic and political competition makes the ethical conduct of public officials a governance issue with domestic and international implications. However, repeated cases of insensitive communication, abuse of authority, and corruption have weakened public trust and exposed a gap between formal codes of conduct and everyday official behavior. This study asks: how do attitudes toward behavior, subjective norms, and perceived behavioral control explain the transformation of ethical responses among Indonesian public officials in digitally mediated controversies? Using qualitative content analysis, the study examines online news narratives, official statements, party releases, social media clarification videos, and available institutional responses from August to September 2025. Sources were selected based on relevance, cross-source confirmation, institutional origin, publication credibility, and traceability of direct quotations to reduce media-framing bias. The results of the study indicate that the transformation of ethical behavior among public officials in Indonesia is influenced by attitudes toward behavior, subjective norms, and perceived behavioral control. This study emphasizes the importance of public officials’ perceptions of their behavioral control as crucial to their ethics. Additionally, it clarifies that ethical literacy based on self-awareness and public oversight is crucial for building a strong governance culture in Indonesia. Ethical literacy programs for public officials need to emphasize the formation of moral awareness and social responsibility through ongoing public oversight and participation.